PENERAPAN INTEGER LINEARPROGRAMMING DALAM PENENTUAN RUTE PENGANGKUTAN SAMPAH DI KOTA KEFAMENANU - rina lemos; Fried Markus Allung Blegur Allung Blegur; Oktovianus R. Sikas; Miko Purnomo (Program Studi Matematika, Universitas Timor, 2026)
ABSTRACT With population growth, waste management issues in Kefamenanu City, North Central Timor Regency, have become a challenge due to limited fleet and personnel. This has resulted in an uneven distribution of workload and waste buildup on some routes. This study aims to optimize garbage transport routes to minimize the total travel distance and ensure an equitable distribution of workload among teams. The method used is Integer Linear Programming (ILP). Primary and secondary data were collected through observation and interviews at the Environmental Agency of North Central Timor Regency (DLH TTU). A mathematical model was formulated to minimize travel distance while considering constraints such as waste volume at temporary disposal sites (TPS), truck capacity, and the requirement that each TPS is served once. The research results show that by applying ILP, the total travel distance was reduced to 106,733 meters from 111,105 meters, a saving of 4,372 meters. The workload distribution also became more balanced.